A42 Transportation, Air pollution and Physical ActivitieS (TAPAS): A comprehensive research programme on active travel. Issue 2 (June 2015) - de Nazelle, Audrey; Rojas-Rueda, David; Jerrett, Michael; Rodriguez, Daniel; Cole-Hunter, Thomas; Donaire, David; Jovanovic Andersen, Zorana; Nieuwenhuijsen, Mark
Abstract: Background: Encouraging walking and cycling as means of transportation may have diverse benefits, such as reduced pollutant emissions and increased physical activity in the population. At the same time, individuals who shift to active travel modes may also experience increased risks of traffic injuries and inhalation of air pollutants. The purpose of the TAPAS research programme ( 2009-2013) was to help decision makers design urban policies that tackle climate change and promote health-related outcomes in Europe, while minimizing potential risks from air pollution and traffic accident. Methods: The central approach of the multi-city and multi-disciplinary study was the development of quantitative health impact assessment models to assess overall impacts of active travel policies, complemented by targeted studies to address research gaps on related topics. In particular, we investigated whether increased physical activity and air pollution interacted to increase health risks. Methods included epidemiologic analyses, cross-over real-world exposure-health experiments, activity and air pollution monitoring, travel surveys, and simulation models. Results: The health impact assessments indicated that the physical activity-related benefits of active travel were greater than the risks associated with increased air pollution inhalation and traffic injuries in each of the 6 cities investigated (Barcelona, Basel, Copenhagen, Paris, Prague, Warsaw). Epidemiologic analyses from our targeted studies confirmed this finding. Benefits of physical activity were found even when exposed to high pollution, but were greater in areas of low to moderate air pollution (e.g. respiratory mortality and cycling hazard ratio 0.55, 95% confidence interval 0.42, 0.72). No significant interactions were found between air pollution and physical activity in triggering adverse health effects in either epidemiologic or experimental studies. Commute times were shown to contribute significantly to overall air pollution exposure, despite the short exposure periods, and ignoring such information led to bias of health effects estimates. Survey analyses showed some potential for policies such as bike lanes and bike sharing systems to increase active travel, which in turn could increase physical activity in the population. Conclusions: Population health benefits can be expected from policies aimed at increasing walking and cycling, despite concerns of increased air pollution exposure while physically active in travel microenvironments. To assess the full extent of such benefits further research is needed to understand the types of policies that are most effective in encouraging active travel, the characteristics of individuals who are most likely to shift to active travel modes, and optimal environmental and personal risk trade-off profiles.